Didactic Possibilities of Webquest Technology in Developing Creative Competence of Future English Language Teachers - Jumayeva, Umida Farhod qizi; Moydinova, Elmira Kamariddinovna (The Lingua Spectrum, 2026)
This article examines the didactic potential of WebQuest technology in developing the creative competence of future English language teachers. Developed in 1995 by the American educator Bernie Dodge, WebQuest is defined as an innovative educational technology based on the purposeful use of Internet resources. The study focuses on key components of creative competence, including creative thinking, non-standard problem solving, independent decision-making, and the ability to produce original ideas and creative products. The article also highlights the role of WebQuest technology in fostering critical and creative thinking, independent learning, collaborative work, and information-communication competencies among students. In addition, the characteristics of short-term and long-term WebQuests, their integration into the educational process, and effective methods of application in teacher training are discussed in detail. The findings demonstrate that systematic use of WebQuest technology increases students’ motivation, enhances practical learning activities, and significantly improves the creative competence of future English language teachers in modern education.